Juventude, violência simbólica e corpo : desvelando relações de poder no cotidiano escolar - Cerqueira, Fabíola dos Santos (2010)
This work aims to investigate the relations among youth, perfect body and symbolic violence in the school environment, relationship that deserve attention, especially if taken into consideration the efforts constant of the midia in to reinforce of “perfect body”, excluding all fleening “baking tin”. Privilegers the quarrel of the body in the perspective of culture, approach antropol, aiming to realize concerning of this body with the processes of youth sociability, in the school environment, especially with the obvious of the violence. As research subjects younger students of the Basic Education Grades of the Public School City State of Vitória/ES. It adopts a study case of type ethnographic combining the following technique for collecting data: application of questionnaire, observation, minute record in the daily field, groups semistructured individual interviews and focus. Notes that youngs the daily discriminated against, ridiculed and rejected, mainly by selves colleagues, because don’t have perfect body. Contained that this process of discrimination is to adopt by school and your professionals that there are when overlook such conduct, when don´t problematize or even when don’t adequate services to individuals of child victims of such exclusion, allowing such attitudes be repeated continuously . Further finds that strategies used by these young are varied: there were who isolate themselves in an attempt to become invisible in the eyes of others, who lead in the game and there was too who hold the press and prefer to leave school. Converses with the following authors: José Machado Pais, Mario Margulis, Luiza Mitiko Yshiguro Camacho, Juarez Dayrell, Pierre Bourdieu, Marilena Chaui, Michel Foucault, Claude Fischer, José Carlos Rodrigues, Everardo Rocha, among others.